The Home and Community Social Behaviour Scales (HCSBS): dimensionality in social competence and antisocial behaviours. Issue 4 (1st October 2016) - Hukkelberg, Silje; Ogden, Terje
ABSTRACT: The study investigated dimensionality in the Home and Community Social Behaviour Scales (HCSBS) that assess social competence (Peer Relations and Self-Management/Compliance) and antisocial behaviour (Defiant/Disruptive and Antisocial/Aggressive behaviour) in children and adolescents. The four scales comprising 64 items were completed by 551 parents of children aged 2–12 with emerging or present behavioural problems. Exploratory and confirmatory factor analyses were used to investigate the latent factor structure of the scales. The results revealed a meaningful three-factor solution for items within each of the following subscales: Peer Relations, Self-Management/Compliance, Defiant/Disruptive, and Antisocial/Aggressive. However, findings revealed some significant cross-loadings within each of the scales. Implications of the results are discussed.